2007
DOI: 10.1111/j.1745-7254.2007.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Neocartilage formation from predifferentiated human adipose derived stem cells in vivo

Abstract: Aim: To examine the chondrogenic potential of human adipose derived stem cells (hASC) induced by human transforming growth factor beta2 (hTGF beta2) in vitro, and to investigate if predifferentiated hASC can produce neocartilage in vivo. Methods: hASC were isolated from subcutaneous adipose tissue and cultured in pellets with the addition of hTGF beta2. Chondrogenic differentiation was assayed by RT-PCR, Western blotting, toluidine blue staining, and immunohistochemistry staining for collagen type II. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…24 As demonstrated by the work of Barry et al, 1 TGF-b 2 and b 3 isoforms have stronger chondrogenic potential than TGF-b 1 . This point was also confirmed in our unpublished data.…”
Section: Discussionmentioning
confidence: 85%
“…24 As demonstrated by the work of Barry et al, 1 TGF-b 2 and b 3 isoforms have stronger chondrogenic potential than TGF-b 1 . This point was also confirmed in our unpublished data.…”
Section: Discussionmentioning
confidence: 85%
“…Variable number of stem cells is present in different tissues such as liver, heart, kidney, skin, bone marrow, adipose tissue, placenta, dental, amniotic fluid, amnion and umbilical cord blood as well as in various fetal tissues (Wei et al 2000;Banas et al 2007). Earlier it was considered that stem cells can only differentiate into mature cells of the same organ but recent evidences have shown that they can also differentiate into other cell types and even into the cells of ectoderm, mesoderm and endoderm (Beltrami et al 2001;De Ugarte et al 2003;Jin et al 2007;Vieira et al 2010;Ren et al 2012). It has been demonstrated that MSCs include a heterogeneous population of cells with multilineage differentiation potential, ability to modulate oxidative stress, and produce a variety of factors that are capable of manipulating a broad range of biological functions (Caplan 2007).…”
Section: Characterization and Application Of Adscsmentioning
confidence: 99%
“…The isolation method and the cytological characterization of stromal precursor cells from adipose tissue were shown at the beginning of the 1970s (Poznanski et al 1973). ADSCs have been obtained from bovine, dog, goat, horse, rabbit, rat, mouse, pig and human (Noer et al 2006;Vidal et al 2007;Jin et al 2007;Torres et al 2007;Yamamoto et al 2007;Williams et al 2008;Vieira et al 2010;Hall et al 2010;Nakanishi et al 2011;Abd El Samad 2011;Ren et al 2012;Strioga et al 2012;Ahmad and Shakori 2013). It has been published for ADSCs that liposuction side, liposuction procedure, variations in the isolation techniques, growth media, culture conditions, age or body mass index play an important role in the cell yield, growth, and frequency of stem cells causing a remarkable difference in their proliferation and differentiation capacity (Tsai et al 2006;Jurgens et al 2008;Baer et al 2012).…”
Section: Characterization and Application Of Adscsmentioning
confidence: 99%
See 2 more Smart Citations